Takemusu Aiki: Insights into Optimizing Ideational Flow - Bradford, Mark (Massey University, 2008)
This paper will investigate how designers can connect broader understandings of ‘leadership’with specific design knowledge to enhance creative performance. The emphasis is on how designers can potentially ‘manage’ their thinking within the ideation process – maximise “ways”to spread ‘memes’. A meme is a rule, concept, or idea that can be spread from one person to another. Designers have been described as ‘memetic engineers’ (Dawkins, 1989) because they produce memes or units of cultural information that are recycled and evolve over time. Memes emerge through ‘imitation and recombination’ according to Blackmore (1999), by mixing up ideas to produce new combinations. One approach to understanding and reflecting on existing disciplinary experiences, as well as challenging creative potential, is through researching other conative “ways” – such as ‘Aikido’ – to embrace and reflect on ‘how’ we think instead of purely ‘what’ we think.
The Fourth Art of Management and Organization Conference, Banff, Canada, 9-12 August 2008
Keywords: Creativity; Co-creation; Aikido; Design; Design leadership